Bannockburn : the Scottish War and the British Isles, 1307-1323 - Brown, Michael, 1965- (Edinburgh University Press, 2008)
The battle of Bannockburn, fought on the fields south of Stirling at midsummer 1314, is the best known event in the history of Medieval Scotland. It was a unique event. The clash of two armies, each led by a king, followed a clear challenge to a battle to determine the status of Scotland and its survival as a separate realm. As a key point in the Anglo-Scottish wars of the fourteenth century, the battle has been extensively discussed, but Bannockburn was also a pivotal event in the history of the British Isles. This book analyses the road to Bannockburn, the campaign of 1314 and the aftermath of the fight. It demonstrates that in both its context and legacy the battle had a central significance in the shaping of nations and identities in the late Medieval British Isles. Key Features A new and unique study of a defining event in British history. Examines to role of the whole British Isles in the Scottish War, giving a sense of the interplay of different lands and communities in the early 14th Century. Addresses the issues and interests at stake in the war beyond simply the rival claims of Robert Bruce and Edward II. Unique focus on the aftermath and legacy of the battle.